Behandlungsbelastung am Lebensende bei Lungenkrebspatienten: Einfluss von unterschiedlichen tumorspezifischen Maßnahmen und unterschiedlichen Gruppendefinitionen auf die Beurteilung der Qualität = Treatment of terminally ill cancer patients : influence of various tumor-specific measures and different group definitions on assessment of quality - Oorschot, Birgitt van; Eschbach, Corinna (Der Onkologe, 2016)
BackgroundIn addition to outcome parameters reported by patients, quality indicators (QI) derived from clinical data are also used internationally to assess the quality of end of life treatment for cancer patients.ObjectiveTo determine the relevance of clinical QI for lung cancer patients and the feasibility of collecting these data in the clinical context and from cancer registries.MethodsA literature review and a survey of four German centers were carried out.ResultsThe large variance observed in patients with tumor-specific therapy in the last 14 days of life can be explained by the variation in the type of survey (e.g. prospective vs. retrospective, survey within the framework of studies or based on registry or insurance data) as well as different definitions of the basic population, e.g. different tumor entities, exclusion of patients younger than 65 years when using the SEER databank and exclusion of patients who died shortly after the diagnosis. Data on tumor therapy in the last 14 days of life could be obtained with little effort both clinically and using regional cancer registries; however, compilation of data from patients in a hospice or specialized palliative care contact as well as finding advance directives (e.g. inspection of patient charts) was much more complicated.ConclusionThe documentation of tumor-specific therapy in the last 14 days of life allows a reflection on the oncological care for terminally ill patients. If the same basic population data are used for the numerator and denominator, comparative analyses between countries and medical centers are possible.
Gesehen am 11.01.2018